Zinc Monotherapy as an Alternative Treatment Option for Decompensated Liver Disease due to Wilson Disease? - Hansa Haftu; Mohammed Mustefa; Teklu Gebrehiwot (Case Reports in Hepatology)
Background. Wilson disease is a rare metabolic disorder involving copper metabolism, and patients may present with a variable degree of hepatic, neurologic, and psychiatric manifestations. In the case of hepatic presentation, treatment is usually initiated with potentially toxic copper chelators (D-penicillamine or Trenton). Although zinc is of low toxicity and low cost for treatment of Wilson disease, it has been limited to the adjunctive as a single maintenance drug or for asymptomatic patients. The use of zinc monotherapy in patients suffering from a severe liver disease was not well studied. In our case report, we describe a pediatric patient who presented with liver failure and the use of zinc monotherapy in patients with severe hepatic manifestations. Case presentation. A 15-year-old male patient from Ethiopia presented with generalized body swelling (edema and ascites) with yellowish discoloration of his eyes and easy fatigability. He had hyperbilirubinemia, coagulopathy, hypoalbuminemia, and deranged liver enzymes. He had a Keyser–Fleischer ring visible with the naked eye, which was confirmed by slit-lamp examination. He had very low serum ceruloplasmin (<8 mg/L) and high 24-hour urine copper (150 mcg/dl). In accordance with the scoring system proposed by the 8th International Meeting on Wilson Disease and Menkes Disease, a diagnosis of Wilson disease was made. Zinc monotherapy with low copper diet was initiated for decompensated liver disease due to Wilson disease because of the inaccessibility of chelators (D-penicillamine or Trientine). After months of treatment with zinc, the patient experienced normalization of hepatic synthetic function and resolution of hypoalbuminemia and coagulopathy. The patient had also clinically stabilized (ascites, lower extremity swelling, edema, and jaundice were improved. Currently, the patient is on follow-up almost for the last four years in the gastrointestinal clinic. Conclusion. Our case shows that zinc has the potential for treatment in improving liver function. Though zinc has its own side effects, it is important and maybe an alternative treatment option in those with limited resources (not able to access chelators). This example hopefully will encourage future investigations and researches on zinc monotherapy for treating symptomatic decompensated hepatic Wilson disease.